2005
DOI: 10.1016/j.femsim.2005.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The humoral immuneresponse toHelicobacter pyloriinfection in children with gastrointestinal symptoms

Abstract: The prevalence of Helicobacter pylori is high in Eastern Europe. The purpose of this study was to estimate the prevalence of H. pylori in symptomatic Lithuanian children and to identify the infection by clinicopathological and serological analyses. One hundred sixteen symptomatic children (age 8-16) with gastritis and duodenal ulcer were included. Biopsies were histologically assessed according to the Sydney-System. Serum IgG antibodies against H. pylori were detected by an enzyme-linked immunosorbent assay (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
2
15
0
1
Order By: Relevance
“…It has been previously reported that there was a positive correlation between H. pylori antibodies and food allergy manifested by gastrointestinal symptoms (24). In the current study, the results revealed a statistically significant (P < 0.01) positive correlation between H. pylori infection and gastrointestinal symptoms (recurrent abdominal pain, vomiting and chronic anorexia) and such results are consistent with that described previously by some investigators in Eastern Europe (11). On the other hand, it was reported that H. pylori infection in India was not associated with recurrent abdominal pain (25).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been previously reported that there was a positive correlation between H. pylori antibodies and food allergy manifested by gastrointestinal symptoms (24). In the current study, the results revealed a statistically significant (P < 0.01) positive correlation between H. pylori infection and gastrointestinal symptoms (recurrent abdominal pain, vomiting and chronic anorexia) and such results are consistent with that described previously by some investigators in Eastern Europe (11). On the other hand, it was reported that H. pylori infection in India was not associated with recurrent abdominal pain (25).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, there is a good correlation between ELISA antibody test and rapid urease test, which afford confirmatory diagnosis of H. pylori infection (10,11). In this study, serum samples were assessed through ELISA for the presence of anti-H. pylori IgG antibodies against high molecular weight cell-associated protein (HM-CAP) of H. pylori using the HM-CAP ELISA kit (EZ-EM Inc., Westbury, NY, USA) as described previously (12).…”
Section: Anti-h Pylori Antibodies Testmentioning
confidence: 99%
“…Nowdays, the importance of Helicobacter pylori infection is increasing as the main causative factor in gastric diseases in humans. This bacterium is highly prevalent in many countries [3] and it increases the risk for development of gastric and duodenal ulcer disease, gastric cancer, and gastric mucosa-associated lymphoid tissue lymphoma [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The same study revealed gender-related differences in H. pylori prevalence among gastric cancer patients, suggesting that in Lithuania H. pylori could be more important for development of gastric cancer in females, whereas smoking and alcohol consumption as risk factors have a stronger impact in males [32]. However, differences in smoking and alcohol consumption could not fully explain the gender-related difference in the prevalence of H. pylori in the study, and other, yet unknown, host and environmental factors might also be important in the development of gastric cancer.…”
Section: Gastric Cancer In the Baltic States - Better Outcomes Are Exmentioning
confidence: 99%